Characterization of a unique copper resistance gene cluster in Xanthomonas campestris pv. campestris isolated in Trinidad, West Indies - Behlau, Franklin; Gochez, Alberto Martin; Lugo, Alshia Janel; Elibox, Winston; Minsavage, Gerald V.; Potnis, Neha; White, Frank F.; Ebrahim, Mohamed; Jones, Jeffrey B.; Ramsubhag, Adesh (Springer, 2018)
Whole genome sequencing of a copper resistant (CuR) black rot strain of Xanthomonas campestris pv. campestris (Xcc) isolated from a broccoli plant in Trinidad revealed a unique operon for copper resistance. The cop genes of strain Xcc-BrA1 were determined to be present on a 160 to 180 kb plasmid shown to be non-conjugative with other xanthomonads. While nucleotide comparison of a putative 8.0 Kbp copLABMGF gene cluster identified in Xcc-BrA1 genome did not reveal any homologous region with other known CuR Xanthomonas strains from diverse origins, the comparison of the translated amino acid sequence indicated similarity with X. citri, X. c. pv. citrumelonis and X. vesicatoria Cop proteins. Cloning of the copLAB gene cluster from Xcc-BrA1 conferred copper resistance to other copper-sensitive xanthomonads. Although Xcc-BrA1 harbors copLAB genes with similar sizes and organization and is able to grow on Cu-amended medium as other CuR xanthomonads, the phylogenetic analysis of nucleotide sequences indicates that the cop cluster in Xcc-BrA1 is unique and distantly related to other copLAB genes from Xanthomonas and Stenotrophomonas. The origin of copper resistance genes in Xcc-BrA1 is likely a result of horizontal gene acquisition from a still unknown phylloplane cohabitant. The findings of this study have implications for the management of crop diseases caused by CuR xanthomonads. Future studies could focus on and determining the distribution, overall importance and appropriate control measures for strains harbouring these unique genes.